Parental Teaching of Reading and Spelling Across the Transition From Kindergarten to Grade 1 - Silinskas, Gintautas; Aunola, Kaisa; Lerkkanen, Marja-Kristiina; Raiziene, Saule (Frontiers in Psychology, 2021)
We investigated the longitudinal links between parental teaching of reading and spelling and children’s word reading and spelling skills. Data of 244 Lithuanian parent–child dyads were analyzed, who were followed across three time points: end of kindergarten (T1; Mage = 6.88; 116 girls), beginning of Grade 1 (T2), and end of Grade 1 (T3). The children’s word reading and spelling skills were tested, and the parents answered questionnaires on the frequency with which they taught their children reading and spelling. Overall, the results showed that the parents were responsive to their children’s skill levels across the domains of reading and spelling and across time (i.e., the transition from kindergarten to Grade 1 and across Grade 1). However, differences between the domains of reading and spelling were also observed. In particular, in the domain of reading and across the transition from kindergarten to Grade 1, the parents responded to their children’s skill levels by increasing the time spent teaching children with poor word reading skills, and decreasing the teaching time for the children with good word reading skills. In contrast, as spelling skills may require more time to develop, parents maintained similar frequencies of teaching spelling across the transition to Grade 1 for all children, and only parents of good spellers taught less spelling at the end of Grade 1 than parents of children with poor and average word spelling skills.